EKSTRAKSI MINYAK ATSIRI DARI DAUN DAN BATANG CENGKEH DENGAN METODE HYDRO-DISTILLATION DAN STEAM-HYDRO DISTILLATION UNTUK MENINGKATKAN NILAI TANAMAN CENGKEH DAN MENENTUKAN PROSES EKSTRAKSI TERBAIK - Santoso, Joko; Hutama, Fajar Mardhi; Lystyoarti, Fatina Anesya; Nilatari, Lidya Linda (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The largest component contained in clove oil is eugenol by 70-80%. The purpose of this research is to study the process of extracting cloves oil use steam-hydro distillation and steam distillation method by microwaves. In addition, studying the factors that influence the extracting process such as power of microwaves, treatment of materials (mesh size 8 and 4 mesh), and the mass of material to the yield and quality of clove oil produced. The operating conditions for these two methods is the mass of 50, 80, 140, and 170 grams, atmospheric pressure (1atm), and temperature of 110oC steam. From the research, can be concluded that the hydro steam distillation method is the best extraction process.Keywords: Â clove oil, eugenol, steam hydro distillation